Development of silvopastoral systems in the Peruvian Amazon - Fuentes Navarro, Eduardo; Gómez, Carlos; Pizarro, Dante; Alegre, Julio; Castillo, Miguel S.; Vela, Jorge; Huamán, Ethel; Vásquez Pérez, Héctor Vladimir (Springer Nature, 2023)
Pasture-based livestock systems in the Peruvian Amazon region are characterized by degraded pastureland and their association with deforestation processes. Silvopastoral systems are an alternative to traditional tree-less pastures that has been recently developed and studied in this region of the country. This chapter provides information about the progress in the development of silvopastoral systems (SPS) in the Peruvian Amazon and the perspectives at national level for the next years. To accomplish these goals, we first review the experiences of establishing and evaluating SPS in five departments of the Peruvian Amazon. Then, we present a list of barriers for the implementation of SPS practices in the country and the current initiatives at the regional and national levels to promote and develop sustainable livestock production systems in the Peruvian Amazon region. We conclude that barriers such as available technology, capacity building, market access and associativity, financing and favorable environmental conditions need to be cleared first for the promotion and successful implementation of SPS in the Peruvian Amazon. Moreover, some of them need to be assumed by the producers, and others by the State at local, regional and national levels.